Critical thinking in Islamic law: the search for strategies - Haneef, Sayed Sikandar Shah; Mahmud , Mek Wok (Universiti Malaya, 2010)
Critical thinking is an intellectual process where it plays a dynamic role in the reconstruction of human thoughts. In Islamic legal thought, this intellectual tool was pivotal in building a full-fledged system of jurisprudence during the glorious days of Islamic civilization. With the solidification of the science of Islamic legal theory and the entrenchment of classical Islamic jurisprudence, this process was somewhat neglected. Recent Islamic revival movements propelled a great zeal for reinstating this process once again. However, the current debate surrounding this concept is not only locked in theoretical intellectualization but also is yet to yield a universally acceptable strategic framework for materializing it in jurisprudential work. This article, therefore, attempts to briefly delineate the concept, unveil the reality on ground and identify some strategies for the application of critical thinking in Islamic law.